2019
DOI: 10.2337/dc19-0184
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequality in Metabolic Control Among Children With Type 1 Diabetes: A Nationwide Longitudinal Study of 4,079 Danish Children

Abstract: To examine inequality in glycemic control by maternal educational level among children with type 1 diabetes in a setting with universal access to health care. RESEARCH DESIGN AND METHODS This was a longitudinal nationwide study of 4,079 Danish children with type 1 diabetes between the years 2000 and 2013. Children were divided into four groups based on mothers' education prebirth (£high school [n = 1,643], vocational or 2-year college [n = 1,548], bachelor's degree [n = 695], ‡master's degree [n = 193]). Means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 32 publications
5
31
0
Order By: Relevance
“…For example, as shown in ESM Fig. 1, the association between headache and poor metabolic control is attenuated when controlling for SES, and lower SES has also previously been linked to poor glycaemic control [27]. Nevertheless, the fact that SES is controlled for and the lack of any stark Fig.…”
Section: Discussionmentioning
confidence: 92%
“…For example, as shown in ESM Fig. 1, the association between headache and poor metabolic control is attenuated when controlling for SES, and lower SES has also previously been linked to poor glycaemic control [27]. Nevertheless, the fact that SES is controlled for and the lack of any stark Fig.…”
Section: Discussionmentioning
confidence: 92%
“…As previously hypothesized, differences in child-rearing practices (24), access to and cost of device use (24), individual type 1 diabetes management practices (31), education (31), expectations (32) specific to device use, maternal education level (33), and patient and provider factors (34) may also contribute to the observed difference between the two registries. Cost of insulin is higher in the U.S. than other countries, and this cost continues to increase (35,36).…”
Section: Discussionmentioning
confidence: 95%
“…However, youth with public insurance in the United States use CGM at lower rates than those with private insurance 8,9 . In addition, data have consistently demonstrated that youth who have public insurance or are of low socioeconomic status (SES) have higher mean HbA1c, higher rates of diabetic ketoacidosis, and lower diabetes related quality of life measures 11‐17 . We have previously demonstrated that when youth with public insurance are provided CGM, they consistently use them 11 …”
Section: Introductionmentioning
confidence: 99%
“…8,9 In addition, data have consistently demonstrated that youth who have public insurance or are of low socioeconomic status (SES) have higher mean HbA1c, higher rates of diabetic ketoacidosis, and lower diabetes related quality of life measures. [11][12][13][14][15][16][17] We have previously demonstrated that when youth with public insurance are provided CGM, they consistently use them. 11 In this study, we describe CGM use in our publicly insured youth with T1D with a particular focus on understanding the effect of interrupted and uninterrupted CGM use and its association with HbA1c changes.…”
mentioning
confidence: 98%